As long as the Earth endures the Bible, creation and the environment - Moo, Jonathan A. 1975-; Routledge, Robin (Nottingham Inter-Varsity Press, 2014)
Introduction / Jonathan Moo and Robin Routledge -- The doctrine of creation : some theological reflections / Alister McGrath -- 'In the beginning it was very good' : Genesis 1-2 and the environment / David L. Baker -- Cursing and chaos : the impact of human sin on creation and the environment in the Old Testament / Robin Routledge -- Creation and kingship : environment and witness in the Yahweh mālāk Psalms / Jamie A. Grant -- The Spirit and the renewal of creation : an Old Testament perspective / David G. Firth -- Destruction or transformation? : Earth's future in biblical perspective / Paul Williamson -- New Testament hope and a Christian environmental ethos / Jonathan Moo -- Paradise by the desolation trail : de-creation and the New Testament / Sean McDonough -- Jürgen Moltmann : creation and the restructuring of trinitarian panentheism / David Rainey -- On being green without playing God : Colin Gunton's environmental ethic / Graham J. Watts -- Does disputing evolution discourage creation care? / R. J. Berry -- Afterword : ethical decision-making / I. Howard Marshall -- Index of scripture references.
For Christians who cultivate theological acuity, so that they see things as God sees them.This stimulating volume offers biblical, theological and scientific perspectives on creation and the environment.You'll be left reflecting God's love and wisdom in how we relate to all he has made. Part of Christian 'discipleship of the mind' is to learn to cultivate theological acuity, so that we see things as God sees them - and act accordingly. 'As Long as the Earth Endures' is a book with regard to creation and our responsibilities in and for it, the light of the gospel of Jesus Christ illumines much that would otherwise remain shadowy and unresolved.Hence, this stimulating volume called 'As Long as the Earth Endures' offers biblical, theological and scientific perspectives on creation and the environment, in the hope that we may learn to see the world more clearly, to perceive its beauty and brokenness when and where we ought, and to reflect God's love and wisdom in how we relate to all he has made
Includes bibliographical references and index
Keywords: Bible; Creation; Ecology -- Environmental aspects; Human Ecology -- Biblical teaching; Human Ecology -- Religious aspects -- Christianity; Ecology ; Environmental aspects; Human ecology ; Biblical teaching; Human ecology ; Religious aspects ; Christianity